La convertibilidad Argentina: ¿un antecedente relevante para la dolarización de Ecuador? - Calcagno, Alfredo (2020)
The adoption of dollarization in Ecuador, throws some doubts about the possibility that Ecuador could face the same problems and challenges that we have observed in other Latin American countries, that decided to apply Tixed exchange rate based policies, without a full dollarization process. The objeotive of this paper, is to discuss some aspects of these Latin American experiences, because similar problems might appear in Ecuador in the near future. The experience discussed is the Argentinean case, where 10 years of convertibility has showed many ains. hortcomines and problems, that hard peg policies can generate, and where the Central Bank must intervene. We highlight, among other factors, that the current situation in Ecuador and the international environment, is very different to the Argentinean case, that prevailed during the launching of the convertibility plan. In Ecuador we don't observe still a strong affluence of capital inflows, nor a big expansion of imports, economic activity and fast stabilization of prices. Also, the ecuadorcan banking system is ina fragile situation, and this impedes a rapid expansion of' the credit supply.